Case Studies for Teaching Special Needs and at-Risk Students - Buzzell, Judith B.; Piazza, Robert (Delmar Publishers, 1994)
Keywords: Case studies; Case studies; Classroom management; Case studies; Problem solving; Case studies; Teaching; Special education; United States; dept.edu; faculty_collection

Instructor's Guide for Case Studies for Teaching Special Needs and at-Risk Students - Buzzell, Judith B.; Piazza, Robert (Delmar Publishers, 1994)
Keywords: Special education; United States; Classroom management; United States; Problem solving; Teaching; dept.edu

A Helping Hand from the Boss. - Granfield, James; LaFontaine, Hernan (1997)
Keywords: Stress management; dept.edu; faculty_collection

The summer stars program - Cantrell, M.L.; Ebdon, S.A.; Firlik, R.; Johnson, D.; Rearick, D. (Educational Leadership, 1997)
Space, futurism, exploration, and stardom are some of the themes at a summer camp inspired by Howard Gardner's theories.
Keywords: dept.bio; dept.edu; peer-reviewed; ⛔ No DOI found

A dynamical systems perspective on mediating violence in schools: emergent roles of child and youth care workers - Vanderven, Karen; Torre, Carlos Antonio (Child Care Quarterly, 1999)
In recent years, violence has been a major concern for human service professionals and increasingly, to child and youth care workers particularly as they have served in schools where major violent events have occurred. Most often violence prevention and intervention efforts ignore the systemic aspects of violence and are too narrowly focused. This article proposes that a consideration of violence in schools be based on dynamical systems theory. This theory offers rich possibilities for generating a useful model for mediating school violence and for suggesting ways in which child and youth care workers can use their competencies to address the multiple factors related to school violence. The article includes an overview to the concepts of dynamical systems theory, offers the dynamical systems model for mediating school violence and presents implications for the roles and functions of child and youth workers particularly in the emerging area of school based child and youth care work. © 1999 Human Sciences Press, Inc.
Keywords: dept.edu

Ritualizing sacredness in math: profaneness in language arts and social studies. - Ensign, Jacque (The Urban Review, 1997)
This paper examines the effect of ritual in different elementary subjects. Lessons in math, language arts, and social studies were observed in public, private, and home school first and fifth grades. In observing these classes, this researcher noted that in all contexts, math lessons were taught very differently from social studies and language arts, confirming earlier work by Stodalsky. The rituals in how concepts were taught, and in how students and teachers related to each other, were very different in math lessons from in the other two subjects. In language arts and social studies lessons, students and teachers routinely shared personal out-of-school experiences, whereas they rarely did so in math lessons. Drawing on Bernstein's description of the sacredness of subjects and linking it to theories in economic anthropology, the author attempts to explain the isolation of school math and to question the level of intimacy and community in current math classes. © 1997 Human Sciences Press, Inc.
Keywords: dept.edu

Reading and spelling difficulties in high school students: Causes and consequences - Shankweiler, Donald; Lundquist, Eric; Dreyer, Lois G; Dickinson, Cheryl C (Reading and Writing, 1996)
Basic skills in reading and spelling and supporting metalinguistic abilities were assessed in ninth and tenth grade students in two school settings. Students attending a private high school for the learning disabled comprised one group and the other comprised low to middle range students from a public high school. Both the LD students and the regular high school students displayed deficiencies in spelling and in decoding, a factor in reading difficulty that is commonly supposed to dwindle in importance after the elementary school years. Treating the overlapping groups as a single sample, multiple regression analysis was used to investigate the contribution of nonword decoding skill and phonological and morphological awareness to spelling ability. The analysis revealed that decoding was the major component, predicting about half of the variance in spelling. The effect of phonological awareness was largely hidden by its high correlation with decoding, but was a significant predictor of spelling in its own right. Morphological awareness predicted spelling skill when the words to be spelled were morphologically complex. An additional study showed that differences in decoding and spelling ability were associated with differences in comprehension after controlling for reading experience and vocabulary. Even among experienced readers individual differences in comprehension of text reflect efficiency of phonological processing at the word level.
Keywords: Decoding; High school poor readers; Metalinguistic abilities; Spelling; dept.edu

Learning to teach, teaching to learn: the center for constructivist teaching-teacher preparation project. - Fosnot, Catherine Twomey (Teaching Education, 1993)
Keywords: dept.edu